Using TikTok as an English Learning Media in the English Language Education Study Program at Wiralodra Indramayu University - Didik Himmawan; Amaliana Rahayu; Leni Nur’aeni; Fikra Fadillah FM (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The social media that is currently popular and widely used is TikTok, based on the report We Are Social Indonesia is in second place with the number of active TikTok users of 99.1 million people. the average Tiktok user in Indonesia, especially teenagers and students, uses 9 hours per day to watch Videos on Tiktok. Therefore, lecturers or teachers are also required to make learning activities more interesting by learning English using Tiktok as a medium. This study aims to find out whether Tiktok can be used as a learning medium that students like. The participants of this study were 5 selected students in semester 5 of the English Department of Wiralodra University. The instrument that researchers use is interviews. Researchers use structured interviews and qualitative interviews. From this data, it can be concluded that students of the English Language Education study program at Wiralodra University use TikTok as a learning medium, especially learning English.